2001
DOI: 10.1016/s0020-7292(01)00452-0
|View full text |Cite
|
Sign up to set email alerts
|

Myomectomy during cesarean section

Abstract: With adequate experience and the use of high dose oxytocin infusion (intra- and post-operatively), myomectomy at cesarean section is not as hazardous as many now believe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 0 publications
4
67
0
8
Order By: Relevance
“…It appears to be safe and best reserved for patients with symptomatic fibroids which are in sub-serosal or pedunculated location and in those affecting the lower uterine segment. Ehigiegba et al [2] removed single fibroids when they were well above 5 cm; in their study, most of patients had multiple fibroids which were intramural in location. They did not remove any posteriorly placed fibroids.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It appears to be safe and best reserved for patients with symptomatic fibroids which are in sub-serosal or pedunculated location and in those affecting the lower uterine segment. Ehigiegba et al [2] removed single fibroids when they were well above 5 cm; in their study, most of patients had multiple fibroids which were intramural in location. They did not remove any posteriorly placed fibroids.…”
Section: Discussionmentioning
confidence: 91%
“…Of the nine cases of caesarean myomectomy reported by Exocoutos and Rosati [1], three were complicated by severe haemorrhage necessitating hysterectomy. Ehigiegba et al [2] studied 25 women who underwent caesarean myomectomy. They used high-dose oxytocin intra-operatively and continued its use for 12-24 h postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Ehigiegba AE et al have reported that caesarean myomectomy is safe with average per operative and postoperative bleeding. 19 Enucleation of the fibroid is technically easier in gravid uterus due to extra looseness of the capsule and dissection becomes easier. 20 In Kerala there is a high incidence of fibroid in reproductive women and so there occurrence in pregnancy is also high so, obstetrician should be skilled to perform emergency myomectomy if indicated.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally advised that myomectomy should be avoided as much as possible during cesarean section because of the substantiated risk of significant hemorrhage. However, reports abound of successful myomectomies during cesarean section [48][49][50]. Myomectomies antenatally by laparotomic or laparoscopic approach prior to fetal viability, most especially in the second trimester of pregnancy, have been rarely carried out as a result of intractable pain from a degenerating fibroid; especially if subserosal and pedunculated, large or rapidly growing, or large fibroid (>5 cm) located in the lower uterine segment [2,47,51].…”
Section: Surgery In Pregnant Women With Uterine Fibroidsmentioning
confidence: 99%